CONSOLIDATION OF POETRY, STORY TELLING, AND SPEECH FOR THEIR COMPETITION AT JAMPANG ENGLISH VILLAGE BOGOR - Tito Dimas Atmawijaya; Anita Sari; Laksmy Kusumoriny; Purwanti Taman; Erni Susianti Nainggolan (LPPM Universitas Pamulang, 2020)
The purpose of this project is to give an English training for Jampang English Village (JEV) students while participating in English competition. The object of this project is the students of JEV Bogor. Total physical response (TPR) is using in this method through giving the strategies; how they correctly use their body language when facing English competition and how to interact with the audience while standing in front of the stage. At the end of the activities, the contestants comprehend the techniques of English training related to poetry, short story, and speech.Key words: English, English competition, poetry, story telling, speech